2020
DOI: 10.1111/tbj.13505
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and feasibility of palliative chemotherapy in very elderly patients with metastatic breast cancer

Abstract: In the Netherlands, approximately 1300 women aged ≥75 years die every year of metastatic breast cancer (MBC). Data on palliative chemotherapy (CT) in very elderly patients are rare, and prospective studies appeared cumbersome. Therefore, we retrospectively analyzed the outcome and feasibility of chemotherapy in elderly MBC patients. Records of all patients with MBC aged ≥75 years who received first‐line palliative chemotherapy between January 2000 and December 2014 at two large teaching hospitals in the Nether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Generally, data on palliative chemotherapy (CHT) in very elderly patients are rare: in a recently published paper, Overgaauw et Al. retrieved clinical records of patients older than 75 years who received first-line chemotherapy in 2 large teaching hospitals in The Netherlands between 2000 and 2014, finding only 54 evaluable patients 22 Other different studies on palliative therapy in very elderly patients reported similar difficulties in enrolling this population 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Generally, data on palliative chemotherapy (CHT) in very elderly patients are rare: in a recently published paper, Overgaauw et Al. retrieved clinical records of patients older than 75 years who received first-line chemotherapy in 2 large teaching hospitals in The Netherlands between 2000 and 2014, finding only 54 evaluable patients 22 Other different studies on palliative therapy in very elderly patients reported similar difficulties in enrolling this population 23 .…”
Section: Discussionmentioning
confidence: 99%
“…A disparidade nos graus de toxicidade, bem como a demanda por reduções de dose, convida à reflexão sobre a necessidade de integrar uma visão mais holística na oncologia geriátrica. O envolvimento de uma equipe multidisciplinar, que possa abordar não apenas os desafios médicos, mas também os sociais e psicológicos enfrentados por pacientes idosos, surge como uma estratégia que pode aprimorar a qualidade e a eficácia da gestão do cuidado oncológico nesta população (KRZYZANOWSKA et al, 2021;OVERGAAUW et al, 2020).…”
Section: Navegando Pelo Desafio Da Toxicidade Em Pacientes Oncogeriát...unclassified
“…These cancers can re-emerge as lethal metastases even decades after the initial tumor appears to have been curatively resected, as the breast cancer cells can escape the local tumor, seed distant organs, and become chemo-resistant even before being detected, making targeting of dissemination impractical [ 1 ]. To prolong survival, metastatic breast cancers require intensive and debilitating therapies that are poorly tolerated in the elderly [ 2 ]. Thus, well-tolerated regimens are desirable to forestall or even prevent these recurrent breast cancers.…”
mentioning
confidence: 99%